(untitled) (Journal of Partial Differential Equations, 2024)
We consider the uniform attractors of a 3D non-autonomous Brinkman– Forchheimer equation with a singularly oscillating force ut-γΔ u+au+b|u|u+c|u|^2u+ abla p=f_0(x,t)+ε^-ρf_1(x,tε), for ρ∈[0,1) and ε>0, and the averaged equation (corresponding to the limiting case ε=0) ut-γΔ u+au+b|u|u+c|u|^2u+ abla p=f_0(x,t).Given a certain translational compactness assumption for the external forces, we obtain the uniform boundedness of the uniform attractor A^ε of the first system in (H^1_0(Ω))^3, and prove that when ε tends to 0, the uniform attractor of the first system A^ε converges to the attractor A^0 of the second system.